PERAN BRAND IMAGE SEBAGAI PEMEDIASI PENGARUH KUALITAS LAYANAN TERHADAP CUSTOMER LOYALTY PELANGGAN INDIHOME KOTA DENPASAR - Sekarwangi, Ida Ayu Mirah; Agus Satria Pramudana, Komang (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2023)
The development of existing technology is very rapid, especially in the field of information and communication. The internet is a basic need for this modern society. IndiHome or Indonesia Digital Home is a communication and data service packages such as landlines, internet, and interactive television services. The purpose of this study was to examine and explain the role of brand image as a mediator of the influence of service quality on customer loyalty of IndiHome customers in Denpasar City. The number of samples determined was 120 respondents in Denpasar City using a questionnaire. The sample was determined using a non-probability sampling with a purposive sampling technique. The data analysis technique used is PLS-based SEM, namely Smart Pls. The results showed that service quality had a significant positive effect on customer loyalty of IndiHome customers in Denpasar City. Service quality has a significant positive effect on the brand image of IndiHome customers in Denpasar City. Brand image has a positive and significant effect on customer loyalty of IndiHome customers in Denpasar City. Brand image plays a role as a mediator of the influence of service quality on customer loyalty of IndiHome customers in Denpasar City.